2021
DOI: 10.1093/ofid/ofab049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Follow-up After Hospitalization for COVID-19 at an Italian Tertiary Care Center

Abstract: We evaluated 100 post-acute COVID-19 patients, a median of 60 days (IQR 48-67) after discharge from the Careggi University Hospital, Italy. Eighty-four (84%) had at least one persistent symptom, irrespective of COVID-19 severity. A considerable number of hospital re-admission (10%) and/or infectious diseases (14%) during the post-discharge period was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 17 publications
4
27
0
Order By: Relevance
“…In our study, the frequency of re-admissions before the follow-up visit was 10.2 per cent, mainly for pneumonia, and/or respiratory failure. Similar re-hospitalization rates have been described by other researchers [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the frequency of re-admissions before the follow-up visit was 10.2 per cent, mainly for pneumonia, and/or respiratory failure. Similar re-hospitalization rates have been described by other researchers [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…The most common symptoms were fatigue (42.4%) and dyspnea (37.3%). Similar data were recently reported by four studies evaluating COVID-19 patients 60 [ 6 , 7 ], 90 [ 8 ], and 110 days [ 9 ] after hospital discharge and by a large Chinese study performed 6 months after hospital discharge [ 10 ]. Our data suggest that COVID-19 has a significant impact on patient mental well-being.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of patients testing positive for COVID-19 will not require hospital admission [67] and indeed persisting symptoms may occur in this group too with 47% of women and 33% of men having ≥1 symptom an average of 117 days post COVID-19 infection. [68] In our study between 8% to 28% of patients were re-hospitalised [25, 29, 38, 49, 50, 53] and 61.7% and 66.4% had visited their GP at the time of follow up [38, 50]. Up to 6 months after testing positive for COVID-19, 73% of non-hospitalised patients had visited their GP, a hospital outpatient clinic or been admitted to hospital.…”
Section: Discussionmentioning
confidence: 82%
“…Six studies reported on reattendance to healthcare providers following discharge. [25, 29, 38, 49, 50, 53] Rehospitalisation rate ranged from 8% to 28% at the time of follow-up across the 6 studies. Two studies found that 61.7% and 66.4% of participants had visited a GP between discharge and follow-up [38, 50] and 20.3% of participants had attended an emergency department by 3 months follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a follow-up study of Spinicci et al [37] indicated that symptom persistence after 60 days from hospital discharge was not related to disease severity (83% in mild/moderate vs 85% in severe/critical, P = 0.807) and ICU admission (84% in ICU vs 84% in non-ICU, P = 0.981). Gautam et al [55] followed up COVID-19 patients admitted to hospital ward and intensive treatment unit (ITU) for 4-7 months from disease onset.…”
Section: Disease Severitymentioning
confidence: 96%